Waterproof flame-retardant nylon composite material for battery sealing ring and preparation method of waterproof flame-retardant nylon composite material

Through the specific proportional combination of PA612 and PA9T and the coordinated use of modified thermal fillers and flame retardants, the comprehensive performance of battery sealing ring materials is improved, the problem of insufficient performance of existing materials is solved, and high-performance battery sealing ring materials are realized.

CN119912810APending Publication Date: 2025-05-02XIAMEN JIANENG TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510155531.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing battery sealing ring materials have insufficient comprehensive performance in terms of low water absorption, thermal conductivity, flame retardant properties and mechanical properties, making it difficult to meet the market's demand for high-performance materials.

Method used

The specific proportional combination of two materials, PA612 and PA9T, is used to combine modified thermal fillers, flame retardants and other additives to form a waterproof and flame retardant nylon composite material for battery sealing rings. This material improves thermal conductivity and flame retardant performance through the synergistic effect of the "brick-slurry" layered structure of the modified thermal filler and the flame retardant. At the same time, through the blending effect of PA612 and PA9T, the mechanical properties and low water absorption rate are improved.

Benefits of technology

It realizes excellent mechanical properties, low water absorption, thermal conductivity and flame retardant properties of battery sealing ring materials, meets the market demand of high-performance materials, and ensures the stable performance and safety of battery sealing rings in extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005269434810000081
    Figure BDA0005269434810000081
  • Figure BDA0005269434810000091
    Figure BDA0005269434810000091
Patent Text Reader

Abstract

The invention relates to the technical field of sealing materials, in particular to a waterproof flame-retardant nylon composite material for a battery sealing ring and a preparation method of the waterproof flame-retardant nylon composite material. The waterproof flame-retardant nylon composite material for the battery sealing ring is prepared from the following raw materials in parts by mass: 80 to 100 parts of PA612, 25 to 35 parts of PA9T, 22 to 26 parts of modified heat-conducting filler, 13 to 15 parts of a flame retardant, 8 to 10 parts of stearic acid, 1 to 2 parts of a coupling agent, 0.3 to 0.5 part of an anti-hydrolysis agent and 0.1 to 0.3 part of an antioxidant. The waterproof flame-retardant nylon composite material for the battery sealing ring, which is excellent in mechanical property, low in water absorption rate, good in heat-conducting property and excellent in flame-retardant property, is prepared by carefully selecting and proportioning the raw materials and adopting a specific modification treatment and synergistic action mechanism.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of sealing materials, and in particular to a waterproof and flame-retardant nylon composite material for a battery sealing ring and a preparation method thereof. Background Art

[0002] Nylon, also known as nylon and polyamide fiber, is the largest and most important variety of engineering plastics. Because nylon is non-toxic, light, has excellent mechanical strength, wear resistance and good corrosion resistance, it is widely used in various fields.

[0003] In the field of battery sealing rings, nylon is generally used as the material for battery sealing rings. Due to the complex structure and small wall thickness of battery sealing rings, and the requirement for certain high and low temperature toughness, strength and low water absorption, the performance indicators of the materials used to produce them are very high.

[0004] With the continuous development of technology, battery sealing ring materials have put forward higher requirements for the comprehensive performance of nylon materials in terms of low water absorption, thermal conductivity, flame retardancy, high strength and mechanical properties. Therefore, it is necessary to further improve the traditional nylon material to enhance its comprehensive performance and better meet market needs. Summary of the invention

[0005] The purpose of this application is to address the deficiencies in current technology and to provide a waterproof and flame-retardant nylon composite material for battery sealing rings and a preparation method thereof. The waterproof and flame-retardant nylon composite material for battery sealing rings prepared in this application has excellent mechanical properties, low water absorption, thermal conductivity and flame retardant properties.

[0006] In the first aspect, the present application provides a waterproof and flame-retardant nylon composite material for a battery sealing ring, which adopts the following technical solution: A waterproof and flame-retardant nylon composite material for a battery sealing ring comprises the following raw materials, measured by weight: 80-100 parts of PA612, 25-35 parts of PA9T, 22-26 parts of a modified thermal conductive filler, 13-15 parts of a flame retardant, 8-10 parts of stearic acid, 1-2 parts of a coupling agent, 0.3-0.5 parts of an anti-hydrolysis agent, and 0.1-0.3 parts of an antioxidant.

[0007] By adopting the above technical solutions, PA612 and PA9T: These two materials together provide the mechanical properties and low water absorption of the composite material. The high tensile strength and impact strength and transparency of PA612 combined with the low water absorption of PA9T make the composite material have good comprehensive properties. Modified thermal conductive filler: The composite of pre-modified boron nitride nanosheets and silicon nitride nanosheets with graphene oxide enhances the thermal conductivity of nylon composites. These fillers improve the thermal conductivity of the material by forming a "brick-paste" layered structure and nanocellulose as a skeleton structure of the thermal conductive channel network. Flame retardants: Flame retardants such as diethyl aluminum hypophosphite, ammonium polyphosphate and magnesium hydroxide work together on the flame retardant properties of the material through different mechanisms. Diethyl aluminum hypophosphite decomposes to form non-volatile aluminum phosphate and an expandable carbon layer, while capturing free radicals produced by combustion; ammonium polyphosphate decomposes to produce non-flammable gases and absorb heat; magnesium hydroxide reduces the temperature and forms a protective layer by absorbing a large amount of heat. Attapulgite clay isolates oxygen by losing water and producing an oxide isolation layer to enhance the flame retardant effect. Stearic acid, coupling agent, anti-hydrolysis agent and antioxidant: These additives improve the waterproof performance, dispersibility and stability of the material respectively. Stearic acid improves the waterproof performance of the material; coupling agent improves the dispersibility and compatibility of fillers in nylon; anti-hydrolysis agent and antioxidant prevent the material from degradation due to moisture and oxidation respectively. In summary, while these components play their respective roles in the composite material, they also form a synergistic effect through interaction, jointly improving the mechanical properties, thermal conductivity, flame retardancy and waterproof properties of the material. This synergistic effect ensures that the battery seal can maintain stable performance and safety in extreme environments.

[0008] Preferably, the mass ratio of the PA612 to the PA9T is 4:1, and the melt flow rate of the PA9T is 10-20 g / 10 min (320° C., 2.16 kg).

[0009] By adopting the above technical solution, PA612 has the advantages of relatively small width, lower density, good dimensional stability, high tensile strength and impact strength, and high transparency in addition to the general PA characteristics. PA9T has the advantage of low water absorption. After PA612 and PA9T are compounded in a specific ratio, the prepared nylon composite has good mechanical properties and low water absorption. When PA612 and PA9T are blended, PA9T has a lower water absorption and can be dispersed in PA612. The proportion of amide groups in the nylon composite is small, which reduces the probability of amide groups forming hydrogen bonds with water. Therefore, it can reduce the absorption and penetration of water molecules by the nylon composite, playing a structural shielding role.

[0010] Preferably, the method for preparing the modified thermally conductive filler comprises the following steps: S31, dispersing 100 parts of thermally conductive filler in 150 parts of 50% ethanol aqueous solution by weight, obtaining a boron nitride suspension after ultrasonic dispersion, adding 50 parts of tannic acid and 3-5 parts of γ-glycidyloxypropyltrimethoxysilane to the boron nitride suspension, mixing and stirring to react, filtering after the reaction, washing and drying to obtain a pre-modified thermally conductive filler for standby use; S32. According to the mass parts, 100 parts of pre-modified thermally conductive filler, 50 parts of graphene oxide, 6.8 parts of silver nitrate and 700 parts of nanocellulose solution with a mass concentration of 0.9% are stirred and mixed for 1 hour to obtain a reaction solution, 15 parts of 20g / L formaldehyde solution are added dropwise to the reaction solution and stirred continuously for 80-90min, the silver nitrate is reduced to nanosilver particles, and then filtered, washed and dried to obtain a modified thermally conductive filler.

[0011] Preferably, in step S31, the thermally conductive filler is prepared by mixing boron nitride nanosheets and silicon nitride nanosheets in a mass ratio of 1:2-3.

[0012] By adopting the above technical scheme, the pre-modified boron nitride nanosheets and silicon nitride nanosheets in the prepared modified thermally conductive filler will also produce a synergistic effect with graphene oxide during the melt extrusion process. On the one hand, the pre-modified boron nitride nanosheets and silicon nitride nanosheets will significantly enhance the thermal conductivity of the nylon composite material after being compounded with graphene oxide. This is because there is a strong hydrogen bond interaction between the pre-modified boron nitride nanosheets and silicon nitride nanosheets and graphene oxide. Under the action of hydrogen bonds, the two-dimensional boron nitride nanosheets and silicon nitride nanosheets and the one-dimensional graphene oxide can be tightly stacked together after melt extrusion, and are highly oriented along the planar direction to form a "brick-paste" layered structure. This highly oriented, ordered, layered in-plane arrangement will provide good transmission of phonons between adjacent boron nitride nanosheets and silicon nitride nanosheets. A good path can significantly improve the thermal conductivity of the external nylon composite material. At the same time, nanocellulose is used as the skeleton structure of the thermal conductive channel network, and nanosilver particles are generated in situ on its surface by silver nitrate reduction. As a metal, nanosilver particles have a high thermal conductivity and can be combined with pre-modified boron nitride nanosheets and silicon nitride nanosheets and graphene oxide to further improve the construction of the thermal conductive channel network. As nanoscale particles, they have a high specific surface area and can be attached to the surfaces of pre-modified boron nitride nanosheets, silicon nitride nanosheets, graphene oxide and nanocellulose, serving as a "bridge" between pre-modified boron nitride nanosheets, silicon nitride nanosheets and graphene oxide, making it easier for them to contact each other, thereby reducing the interface thermal resistance, thereby significantly improving the mechanical strength, thermal conductivity, low water absorption and flame retardant properties of the nylon composite material.

[0013] Preferably, the flame retardant comprises the following raw materials, calculated by weight: 30-35 parts of magnesium hydroxide, 6-8 parts of ammonium polyphosphate, 12-16 parts of diethyl aluminum hypophosphite, 13-15 parts of attapulgite clay, and 1.3-1.5 parts of silane coupling agent. The average particle size of the magnesium hydroxide is 8-10 μm; the average particle size of the attapulgite clay is 1-2 μm.

[0014] Preferably, the silane coupling agent is at least one of propyltrimethoxysilane, vinyltrimethoxysilane and γ-glycidyloxypropyltrimethoxysilane.

[0015] Preferably, the method for preparing the flame retardant comprises the following steps: S71. Mix magnesium hydroxide, ammonium polyphosphate, diethyl aluminum hypophosphite and attapulgite clay uniformly according to their weight fractions to obtain a mixed material; S72. Add the mixture of step S71 and the silane coupling agent into a high-speed mixer according to their mass fractions. After stirring for 20-30 minutes, raise the temperature to 70-75°C and continue stirring for 80-100 minutes. After the temperature drops to room temperature, discharge the mixture to obtain a flame retardant.

[0016] By adopting the above technical scheme, in the prepared flame retardant, diethyl aluminum hypophosphite produces flame retardant effects through gas phase and condensed phase at the same time. On the one hand, diethyl aluminum hypophosphite produces flame retardant effects by decomposing into non-volatile aluminum phosphate and promoting nylon carbonization, and forms an expandable carbon layer under the action of ammonium polyphosphate. On the other hand, diethyl aluminum hypophosphite decomposes into volatile phosphides, captures free radicals produced by combustion, and inhibits combustion; ammonium polyphosphate produces non-combustible gas by decomposing in the polymer and absorbs the heat generated by the polymer. The composite diethyl aluminum hypophosphite promotes nylon carbonization and the formation of aluminum phosphate, thereby producing a synergistic flame retardant effect. Magnesium hydroxide decomposes and absorbs a large amount of heat, which reduces the temperature of the polymer, thereby slowing down the decomposition and combustion of the polymer; magnesium hydroxide decomposes under heat to release water vapor, which can reduce the temperature of the material and prevent the combustion of the material on the one hand, and can also play a diluting role on the other hand; the decomposed magnesium oxide can form a film on the surface of the burning material, promote the formation of a carbonized layer, and the carbonized layer can enhance the density of the diethyl aluminum hypophosphite and ammonium polyphosphate expanded carbon layer, improve the insulation against heat, oxygen and volatile products, prevent the entry of heat and oxygen, and play a flame retardant role. Attapulgite clay has a good aspect ratio, rich internal pores, and contains a large amount of crystal water. It loses water and produces water vapor in turn at high temperatures, which can isolate oxygen, thereby achieving a flame retardant effect. In addition, under high temperature conditions, an oxide isolation layer mainly composed of magnesium oxide and aluminum oxide can be produced, which has good thermal stability and can inhibit combustion. Attapulgite clay is based on silicon-oxygen tetrahedron as the basic unit. The oxygen atoms in the tetrahedron are filled into the top corners, forming layer chains in an up-and-down staggered form at a certain distance. The layer chains are connected by oxygen atoms to form layered silicate minerals. The flame retardancy of the condensed phase is enhanced through the protective effect of layered silicates, and the synergistic flame retardancy of diethyl aluminum hypophosphite and ammonium polyphosphate is improved.

[0017] The surfaces of magnesium hydroxide and attapulgite clay contain a large amount of positive charges, have strong polarity and hydrophilicity and oleophobicity, and the crystal grains are easy to agglomerate into groups. Their surfaces are hydrophilic and oleophobic, resulting in poor dispersibility and compatibility in polymer materials such as nylon, which has a great influence on the mechanical properties and processability of the materials. In the flame retardant preparation method described in the present application, the powder is modified by a silane coupling agent, and the surface of the powder is oleophilic and hydrophobic, and the dispersibility and compatibility in nylon are good, thereby improving the mechanical properties and waterproof properties of nylon.

[0018] Preferably, the coupling agent is prepared by mixing vinyl trimethoxy silane and γ-glycidyloxypropyl trimethoxy silane in a mass ratio of 3:2-4.

[0019] By adopting the above technical scheme, the dispersibility and compatibility of magnesium hydroxide and attapulgite clay in the nylon matrix can be improved through the chemical action of the coupling agent. This helps to improve the mechanical properties and processing properties of the material. The coupling agent can form a chemical bond between the nylon matrix and the filler, thereby enhancing the adhesion of the interface, reducing the interfacial thermal resistance, and improving the thermal conductivity and mechanical strength of the material. By modifying the filler with a coupling agent, the dispersibility and effect of the flame retardant in nylon can be improved, thereby enhancing the flame retardant properties of the material. Vinyl trimethoxysilane may provide good adhesion and flexibility. γ-Glycidyloxypropyl trimethoxysilane may provide additional chemically active groups that can react with the nylon matrix or other fillers. The mixed use of the two may produce a synergistic effect, that is, the functions of each of the two are enhanced or complementary after mixing, thereby improving the overall performance of the nylon composite material.

[0020] Preferably, the anti-hydrolysis agent is carbodiimide; and the antioxidant is prepared by mixing antioxidant 1010 and antioxidant 1076 in a mass ratio of 3:1.

[0021] In a second aspect, the present application provides a method for preparing a waterproof and flame-retardant nylon composite material for a battery sealing ring, using the following technical solution: A method for preparing a waterproof and flame-retardant nylon composite material for a battery sealing ring, using the raw material of the waterproof and flame-retardant nylon composite material for a battery sealing ring, comprises the following steps: S101, respectively add PA612, PA9T, modified thermal conductive filler, flame retardant, stearic acid, coupling agent, anti-hydrolysis agent and antioxidant into a stirring tank according to their mass fractions, set the speed to 300 rpm, stir for 10-15 minutes, and obtain a mixture; S102. Add the mixed material into the hopper of a twin-screw extruder, extrude, shear and granulate through the twin-screw extruder to obtain a waterproof and flame-retardant nylon composite material for a battery sealing ring; wherein the screw diameter is 60 mm, the aspect ratio of the screw is 40:1, the screw speed is 350 rpm, and the temperatures of each zone of the screw are: 210-220°C in the first zone, 230-240°C in the second zone, 250-260°C in the third zone, 270-275°C in the fourth zone, 280-285°C in the fifth zone, and 275-280°C in the sixth zone.

[0022] In summary, the beneficial technical effects of this application are: 1. Excellent mechanical properties: The mechanical strength of nylon composite materials is improved by compounding PA612 and PA9T in a specific ratio and adding modified thermal conductive fillers. The high tensile strength and impact strength of PA612 and the low water absorption of PA9T combine to give the composite materials good mechanical properties.

[0023] 2. Low water absorption: The low water absorption of PA9T and the reduction in the proportion of amide groups in the nylon composite reduce the absorption and penetration of water molecules by the nylon composite, thereby achieving a structural shielding effect and improving the waterproof performance of the material.

[0024] 3. Thermal conductivity: The pre-modified boron nitride nanosheets and silicon nitride nanosheets in the modified thermal conductive filler are used in combination with graphene oxide to form a highly oriented "brick-paste" layered structure, which significantly enhances the thermal conductivity of the nylon composite material. At the same time, nanocellulose, as the skeleton structure of the thermal conductive channel network, further improves the construction of the thermal conductive channel network.

[0025] 4. Flame retardant properties: The flame retardant properties of nylon composites are improved by using flame retardants such as diethyl aluminum hypophosphite, ammonium polyphosphate, magnesium hydroxide and attapulgite clay, as well as their synergistic effects. These flame retardants can play a role at different levels, including flame retardant effects in the gas phase and condensed phase, heat absorption and dispersion, and the formation of a protective layer for the material.

[0026] 5. Improved dispersibility and compatibility: The powder is modified by silane coupling agent to improve the dispersibility and compatibility of magnesium hydroxide and attapulgite clay in nylon, thereby improving the mechanical properties and processing properties of nylon. DETAILED DESCRIPTION

[0027] The implementation scheme of the present application will be described in detail below in conjunction with the examples, but those skilled in the art will understand that the following examples are only used to illustrate the present application and should not be considered to limit the scope of the present application. If the specific conditions are not specified in the examples, they are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially. Antioxidant 1010 and antioxidant 1076 are produced by Germany's Bassif Company. The melt flow rate of PA9T is 12g / 10min (320℃, 2.16kg), model: Japan Kuraray N1001A.

[0028] In the following Examples and Preparation Examples, 1 part means 100 g.

[0029] Preparation Example 1 Modified Thermally Conductive Filler The preparation method of the modified thermal conductive filler comprises the following steps: S31. Dispersing 100 parts of thermally conductive filler in 150 parts of 50% ethanol aqueous solution by weight, obtaining a boron nitride suspension after ultrasonic dispersion, adding 50 parts of tannic acid and 4 parts of γ-glycidyloxypropyltrimethoxysilane to the boron nitride suspension, mixing and stirring to react, filtering after the reaction, washing and drying to obtain a pre-modified thermally conductive filler for standby use; the thermally conductive filler is prepared by mixing boron nitride nanosheets and silicon nitride nanosheets in a weight ratio of 1:3; S32. According to the mass parts, 100 parts of pre-modified thermally conductive filler, 50 parts of graphene oxide, 6.8 parts of silver nitrate and 700 parts of nanocellulose solution with a mass concentration of 0.9% are stirred and mixed for 1 hour to obtain a reaction solution. 15 parts of 20g / L formaldehyde solution are added dropwise to the reaction solution and stirred for 85 minutes to reduce the silver nitrate to nanosilver particles, and then filtered, washed and dried to obtain a modified thermally conductive filler.

[0030] Preparation Example 2 Preparation of flame retardant The flame retardant comprises the following raw materials, calculated by weight: 33 parts of magnesium hydroxide, 7 parts of ammonium polyphosphate, 14 parts of diethyl aluminum hypophosphite, 14 parts of attapulgite clay, and 1.4 parts of vinyl trimethoxysilane, wherein the average particle size of the magnesium hydroxide is 9 μm; the average particle size of the attapulgite clay is 1.5 μm; The preparation method of the flame retardant comprises the following steps: S71. Mix magnesium hydroxide, ammonium polyphosphate, diethyl aluminum hypophosphite and attapulgite clay uniformly according to their weight fractions to obtain a mixed material; S72. Add the mixture of step S71 and vinyltrimethoxysilane into a high-speed mixer according to their mass fractions. After stirring for 25 minutes, raise the temperature to 74°C and continue stirring for 90 minutes. After the temperature drops to room temperature, discharge the mixture to obtain a flame retardant.

[0031] Example 1 A waterproof and flame-retardant nylon composite material for a battery sealing ring, comprising the following raw materials by weight: 80 parts of PA612, 25 parts of PA9T, 22 parts of a modified thermally conductive filler, 13 parts of a flame retardant, 8 parts of stearic acid, 1 part of a coupling agent, 0.3 parts of carbodiimide, and 0.1 parts of an antioxidant, wherein the coupling agent is prepared by mixing vinyl trimethoxy silane and γ-glycidyloxypropyl trimethoxy silane in a weight ratio of 3:2, and the antioxidant is prepared by mixing antioxidant 1010 and antioxidant 1076 in a weight ratio of 3:1; The raw material of the waterproof and flame-retardant nylon composite material for the battery sealing ring comprises the following steps: S101, respectively adding PA612, PA9T, modified thermal conductive filler, flame retardant, stearic acid, coupling agent, carbodiimide and antioxidant into a stirring tank according to their weight proportions, setting the speed to 300 rpm, stirring for 10 min, and obtaining a mixture; S102. Add the mixed material into the hopper of a twin-screw extruder, extrude, shear and granulate through the twin-screw extruder to obtain a waterproof and flame-retardant nylon composite material for battery sealing rings; wherein, the screw diameter is 60 mm, the aspect ratio of the screw is 40:1, the screw speed is 350 rpm, and the temperatures of each zone of the screw are: 210°C in the first zone, 230°C in the second zone, 250°C in the third zone, 270°C in the fourth zone, 280°C in the fifth zone, and 275°C in the sixth zone.

[0032] Example 2 A waterproof and flame-retardant nylon composite material for a battery sealing ring, comprising the following raw materials by weight: 100 parts of PA612, 35 parts of PA9T, 26 parts of a modified thermally conductive filler, 15 parts of a flame retardant, 10 parts of stearic acid, 2 parts of a coupling agent, 0.5 parts of carbodiimide, and 0.3 parts of an antioxidant, wherein the coupling agent is prepared by mixing vinyl trimethoxy silane and γ-glycidyloxypropyl trimethoxy silane in a weight ratio of 3:4, and the antioxidant is prepared by mixing antioxidant 1010 and antioxidant 1076 in a weight ratio of 3:1; The raw material of the waterproof and flame-retardant nylon composite material for the battery sealing ring comprises the following steps: S101, adding PA612, PA9T, modified thermal conductive filler, flame retardant, stearic acid, coupling agent, carbodiimide and antioxidant into a stirring tank according to their weight proportions, setting the rotation speed to 300 rpm, stirring for 15 min, and obtaining a mixture; S102. Add the mixed material into the hopper of a twin-screw extruder, extrude, shear and granulate through the twin-screw extruder to obtain a waterproof and flame-retardant nylon composite material for battery sealing rings; wherein, the screw diameter is 60 mm, the aspect ratio of the screw is 40:1, the screw speed is 350 rpm, and the temperatures of each zone of the screw are: 220°C in the first zone, 240°C in the second zone, 260°C in the third zone, 275°C in the fourth zone, 285°C in the fifth zone, and 280°C in the sixth zone.

[0033] Example 3 A waterproof and flame-retardant nylon composite material for a battery sealing ring, comprising the following raw materials by weight: 95 parts of PA612, 30 parts of PA9T, 24 parts of a modified thermally conductive filler, 14 parts of a flame retardant, 9 parts of stearic acid, 1.5 parts of a coupling agent, 0.4 parts of carbodiimide, and 0.2 parts of an antioxidant, wherein the coupling agent is prepared by mixing vinyl trimethoxy silane and γ-glycidyloxypropyl trimethoxy silane in a weight ratio of 3:3, and the antioxidant is prepared by mixing antioxidant 1010 and antioxidant 1076 in a weight ratio of 3:1; The raw material of the waterproof and flame-retardant nylon composite material for the battery sealing ring comprises the following steps: S101, adding PA612, PA9T, modified thermal conductive filler, flame retardant, stearic acid, coupling agent, carbodiimide and antioxidant into a stirring tank according to their weight proportions, setting the speed to 300 rpm, stirring for 13 min, and obtaining a mixture; S102. Add the mixed material into the hopper of a twin-screw extruder, extrude, shear and granulate through the twin-screw extruder to obtain a waterproof and flame-retardant nylon composite material for battery sealing rings; wherein, the screw diameter is 60 mm, the aspect ratio of the screw is 40:1, the screw speed is 350 rpm, and the temperatures of each zone of the screw are: 215°C in the first zone, 235°C in the second zone, 255°C in the third zone, 273°C in the fourth zone, 283°C in the fifth zone, and 278°C in the sixth zone.

[0034] Example 4 Same as Example 3, except that PA612 contains 100 parts and PA9T contains 25 parts.

[0035] Comparative Example 1 Same as Example 4, except that PA612 contains 125 parts and PA9T contains 0 parts.

[0036] Comparative Example 2 The same as Example 4, except that an equal amount of mixed filler (prepared by mixing boron nitride nanosheets, silicon nitride nanosheets and graphene oxide in a mass ratio of 1:3:2) is used instead of the modified thermal conductive filler.

[0037] Comparative Example 3 The same as Example 4, except that the coupling agent is vinyltrimethoxysilane.

[0038] Comparative Example 4 The same as Example 4, except that the coupling agent is γ-glycidyloxypropyltrimethoxysilane.

[0039] Performance Testing The waterproof and flame-retardant nylon composite materials for battery sealing rings prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were sampled and made into test strips, and the following performance tests were carried out. The results are shown in Table 1.

[0040] Tensile strength: tested according to ASTM D638 standard; Elongation at break: Tested according to ASTM D638 standard; Bending strength: tested according to ASTM D638 standard; Flexural modulus: tested according to ASTM D638 standard; Notched impact strength: tested according to ASTM D638 standard; Water absorption rate: According to ASTM D570-2005 plastic water absorption test method, immerse at 23 ° C for 24 hours and test the water absorption rate (%); Thermal conductivity test: Tested using ASTM D5470 standard; Flame retardancy: The flame retardancy of the test strips with a thickness of 2 mm was tested according to the UL94-2009 standard.

[0041] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The waterproof and flame-retardant nylon composite materials for battery sealing rings prepared in Examples 1 to 4 have excellent mechanical properties, low water absorption, thermal conductivity and flame retardancy.

[0042] 2) The performance comparison analysis of the waterproof and flame-retardant nylon composite material for battery sealing rings prepared in Example 4, Example 3 and Comparative Example 1 shows that when the mass fraction ratio of PA612 and PA9T is 4:1, the prepared nylon composite has good mechanical properties and low water absorption. When PA612 and PA9T are blended in a specific ratio, PA9T has a low water absorption rate and can be dispersed in PA612. The proportion of amide groups in the nylon composite is small, which reduces the probability of amide groups forming hydrogen bonds with water. Therefore, the absorption and penetration of water molecules by the nylon composite can be reduced, playing a structural shielding role.

[0043] 3) The performance comparison analysis of the waterproof and flame-retardant nylon composite material for battery sealing rings prepared in Example 4 and Comparative Example 2 shows that the pre-modified boron nitride nanosheets and silicon nitride nanosheets in the modified thermal conductive filler prepared in the present application and graphene oxide will also produce a synergistic effect during the melt extrusion process. On the one hand, the pre-modified boron nitride nanosheets and silicon nitride nanosheets will significantly enhance the thermal conductivity of the nylon composite material after being composited with graphene oxide. This is because there is a strong hydrogen bond interaction between the pre-modified boron nitride nanosheets and silicon nitride nanosheets and graphene oxide. Under the action of hydrogen bonds, the two-dimensional boron nitride nanosheets and silicon nitride nanosheets and the one-dimensional graphene oxide can be tightly stacked together after melt extrusion, and are highly oriented along the plane direction to form a "brick-paste" layered structure. This highly oriented ordered layered arrangement will provide a phonon in the adjacent boron nitride nanosheets. The thermal conductivity of the nylon composite material can be significantly improved by providing a good path for transmission between the sheets and the silicon nitride nanosheets. At the same time, nanocellulose is used as the skeleton structure of the thermal conductive channel network, and nanosilver particles are generated in situ on its surface by silver nitrate reduction. As a metal, the nanosilver particles have a high thermal conductivity and can be combined with pre-modified boron nitride nanosheets and silicon nitride nanosheets and graphene oxide to further improve the construction of the thermal conductive channel network. As nanoscale particles, they have a high specific surface area and can be attached to the surfaces of pre-modified boron nitride nanosheets, silicon nitride nanosheets, graphene oxide and nanocellulose, and serve as a "bridge" between pre-modified boron nitride nanosheets, silicon nitride nanosheets and graphene oxide, making it easier for them to contact each other, thereby reducing the interface thermal resistance, thereby significantly improving the mechanical strength, thermal conductivity, low water absorption and flame retardancy of the nylon composite material.

[0044] 4) The performance comparison analysis of the waterproof and flame-retardant nylon composite materials for battery sealing rings prepared in Example 3 and Comparative Examples 3-4 shows that the coupling agent is prepared by mixing vinyl trimethoxy silane and γ-glycidyloxypropyl trimethoxy silane in a mass ratio of 3:3. The synergistic effect of them can improve the overall performance of the nylon composite material.

[0045] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.

Claims

1. A waterproof and flame-retardant nylon composite material for battery sealing ring, characterized in that: The preparation comprises the following raw materials in parts by mass: 80-100 parts of PA612, 25-35 parts of PA9T, 22-26 parts of modified thermal conductive filler, 13-15 parts of flame retardant, 8-10 parts of stearic acid, 1-2 parts of coupling agent, 0.3-0.5 parts of anti-hydrolysis agent, and 0.1-0.3 parts of antioxidant.

2. The waterproof and flame-retardant nylon composite material for a battery seal ring according to claim 1, characterized in that: The mass ratio of the PA612 to the PA9T is 4:1, and the melt flow rate of the PA9T is 10-20 g / 10 min.

3. The waterproof and flame-retardant nylon composite material for a battery seal ring according to claim 1, characterized in that: The preparation method of the modified thermally conductive filler comprises the following steps: S31. Dispersing 100 parts by mass of a thermally conductive filler in 150 parts by mass of a 50% ethanol aqueous solution to obtain a boron nitride suspension after ultrasonic dispersion. Adding 50 parts by mass of tannic acid and 3-5 parts by mass of γ-glycidyloxypropyltrimethoxysilane to the boron nitride suspension, the mixture is mixed and stirred to react. After the reaction is completed, the mixture is filtered, washed, and dried to obtain a pre-modified thermally conductive filler for later use. S32. According to the mass parts, 100 parts of pre-modified thermal conductive filler, 50 parts of graphene oxide, 6.8 parts of silver nitrate and 700 parts of nanocellulose solution with a mass concentration of 0.9% are stirred and mixed for 1 hour to obtain a reaction solution. 15 parts of 20 g / L formaldehyde solution are added dropwise to the reaction solution and stirred for 80-90 minutes to reduce the silver nitrate to nanosilver particles. The mixture is then filtered, washed and dried to obtain a modified thermal conductive filler.

4. The waterproof and flame-retardant nylon composite material for a battery seal ring according to claim 3, characterized in that: In step S31, the thermal conductive filler is prepared by mixing boron nitride nanosheets and silicon nitride nanosheets in a mass ratio of 1:2-3.

5. The waterproof and flame-retardant nylon composite material for battery sealing ring according to claim 1, characterized in that: The flame retardant includes the following raw materials, calculated by weight: 30-35 parts of magnesium hydroxide, 6-8 parts of ammonium polyphosphate, 12-16 parts of diethyl aluminum hypophosphite, 13-15 parts of attapulgite clay, and 1.3-1.5 parts of a silane coupling agent. The average particle size of the magnesium hydroxide is 8-10 μm; the average particle size of the attapulgite clay is 1-2 μm.

6. The waterproof and flame-retardant nylon composite material for battery sealing ring according to claim 5, characterized in that: The silane coupling agent is at least one of propyltrimethoxysilane, vinyltrimethoxysilane and γ-glycidyloxypropyltrimethoxysilane.

7. The waterproof and flame-retardant nylon composite material for battery sealing ring according to claim 5, characterized in that: The preparation method of the flame retardant comprises the following steps: S71. Mix magnesium hydroxide, ammonium polyphosphate, diethyl aluminum hypophosphite, and attapulgite clay in parts by mass to obtain a mixed material; S72. Add the mixture of step S71 and the silane coupling agent into a high-speed stirrer according to their mass fractions. After stirring for 20-30 minutes, raise the temperature to 70-75° C. and continue stirring for 80-100 minutes. Discharge the mixture after the temperature drops to room temperature to obtain a flame retardant.

8. The waterproof and flame-retardant nylon composite material for battery sealing ring according to claim 1, characterized in that: The coupling agent is prepared by mixing vinyltrimethoxysilane and gamma-glycidyloxypropyltrimethoxysilane in a mass ratio of 3:2-4.

9. The waterproof and flame-retardant nylon composite material for battery sealing ring according to claim 1, characterized in that: The anti-hydrolysis agent is carbodiimide; and the antioxidant is prepared by mixing antioxidant 1010 and antioxidant 1076 in a mass ratio of 3:

1.

10. A method for preparing a waterproof and flame-retardant nylon composite material for a battery seal ring, characterized in that: The method of using the raw material of the waterproof and flame-retardant nylon composite material for a battery seal ring according to any one of claims 1 to 9 comprises the following steps: S101. Add PA612, PA9T, modified thermal conductive filler, flame retardant, stearic acid, coupling agent, anti-hydrolysis agent and antioxidant to a stirring tank according to their mass parts, set the speed to 300 rpm, and stir for 10-15 minutes to obtain a mixture; S102. Add the mixed material into the hopper of a twin-screw extruder, extrude, shear, and granulate through the twin-screw extruder to obtain a waterproof and flame-retardant nylon composite material for battery sealing rings; wherein, the screw diameter is 60 mm, the aspect ratio of the screw is 40:1, the screw speed is 350 rpm, and the temperatures of each zone of the screw are: 210-220°C in the first zone, 230-240°C in the second zone, 250-260°C in the third zone, 270-275°C in the fourth zone, 280-285°C in the fifth zone, and 275-280°C in the sixth zone.

Citation Information

Patent Citations

  • Reinforced polyamide moulding compositions and injection mouldings produced therefrom

    CN105504789A

  • Preparation method of high-thermal-conductivity insulating cellulose composite material

    CN116376116A

  • High-thermal-conductivity flame-retardant nylon composite material for battery sealing ring and preparation method thereof

    CN117363006A

  • High-flexibility low-smoke modified power cable based on fluoropolymer sheath and preparation method

    CN117976314A

  • Flame retardant compositions

    CN1667030A